'I love a curry': student-teacher discourse around 'race' and ethnicity at a UK university. Issue 2 (15th March 2018) - Dunne, Linda; Kay, Virginia; Boyle, Rachel; Obadan, Felix; Lander, Vini
Abstract: This paper presents aspects of a small scale study that considered student teachers' language and discourse around race and ethnicity at a university in the northwest of England. The first part of the paper critiques current education-related policy, context and practice to situate the research and then draws upon aspects of critical race theory and whiteness theory as frames of reference. In the research, 250 student-teachers completed questionnaires that invited responses to statements about race and ethnicity and this was followed by two semi-structured group interviews. A discourse analysis approach was taken to analyse the language used in the questionnaire responses and, in particular, the group interviews. Recurrent discursive configurations were characterised by language that signified othering, correct knowledge, personalisation and discomfort. Hesitations and silences during group discussions perhaps intimated thinking time and also maybe a reluctance to talk about aspects of race and ethnicity, and what was not said remains significant. It is suggested that a reconstruction of a teacher/educator subjectivity that fosters self-reflection on values and racial positioning, is needed in teacher education, alongside critical examination of the silences and discomfort surrounding race and ethnicity.